RANCANGAN SISTEM INFORMASI PERHITUNGAN PENYUSUTAN FIXED ASSETS MENGGUNAKAN STRAIGHT LINE METHOD PADA PT FIF GROUP PEMATANGSIANTAR - Ayu Tiara Defi; Dedi Suhendro (LPPM STMIK Lombok, 2021)
PT Federal Internasional Finance (FIF) Group is a finance company whose majority shareholder is PT Astra. The high routine of PT Federal International Finance (FIF) Group has 39 hours of work a week so that PT Federal International Finance (FIF) Group has enough data to manage. For example regarding fixed asset data. Based on observations made by the author, PT Federal International Finance (FIF) Group computes computerized inventory of office inventory depreciation using Microsoft Excel. In office inventory calculations that have 50 inventory data, data redundancy often occurs, such as entering the same inventory name, often repeating and using inefficient time due to the large amount of inventory data that will be inputted into Microsoft Excel. To overcome this problem the authors designed calculations using the Straight Line Method to overcome the use of inefficient time and to avoid duplicate data. The design created is the context diagram design, the Data Flow Diagram (DFD) design, the Entity Relational Diagram (ERD) design, the Inter Table Design (RAT) design. In building this system a system is used, namely Microsoft Visual Basic 6.0 and SQL Server 2000 Database.